Expressividade do Arquivo no Documentário Interativo - Daniel Alberto Rodrigues Correia (2015)
With the evolution of communication technologies, new creative platforms have appeared,whereas others extended.The genre of documentary film, characterized by the expressive strength of its representationof reality, is one of the platforms that have expanded towards a digital, participative and interactiveuniverse. Profiting of the participative nature of the Internet working together with theproperties of New Media (Manovich, 2001), the Documentary now benefits of the different interactionconfigurations among archive objects and "spectators". It is this connection that originatesthe Interactive Documentary, open to new formats able to absorb and recount reality through digitalartefacts while involving the viewer, now participating user. Participative archives bring withthem new dynamics for documentary cinema and new organics of content navigation.Keeping in mind the relevance and objective of the usage of archives along the documentaryfilm's history, this dissertation aims at exploring the expressive potential of new artefacts as integratingparts of the digital archives of Interactive Documentaries.